Risk factors of radicalisation towards violent extremism: challenges and progress - Mohd Rashid, Nurul Miza (IIUM Press, 2020)
Statistics have shown that violent extremism was responsible for tens of thousands of deaths, destructions of properties, and billions of economic losses to multiple nations for years. Despite a wide array of research conducted since the early 1940s, some academics in the past decades believe that studies on risk factors of radicalisation towards violent extremism are hindered by many setbacks causing the field to be at infancy stage in research and knowledge compared to other areas of studies. Challenges faced by academics in the field had caused stagnation in reaching a holistic understanding of radicalisation's risk factors. However, some academics have stressed that it is untrue to refer to the research field as stagnant. It dismisses a multitude of empirical studies published for decades. Some scholars had found that progress has been made, but it is relatively slow due to some research challenges imposed on the field. This paper highlights the challenges that remain true and prevalent to many academics that attempted to study radicalisation's risk factors towards violent extremism. Also, this paper provides some relevant evidence which shows that thenotion regarding the challenges may be true.